HLA-DQ2 and -DQ8 genotype frequency in Syrian celiac disease children: HLA-DQ relative risks evaluation - Hossam Murad; Batoul Jazairi; Issam Khansaa; Doaa Olabi; Lina Khouri (BMC Gastroenterology, 2018)
Abstract Background Celiac disease (CD) is a common autoimmune disease in Syria which manifesting with inflammation of the small intestine and with various extra intestinal symptoms. The disease is associated with human HLA-DQ genes encoding HLA-DQ2 and DQ8 proteins. Methods In this study, 49 children patients of CD and 58 healthy control samples were genotyped for HLA-DQ genes using SSP-PCR technique. Relative risks for different genotypes were also evaluated. Results The DQB1*0201 allele was the most common in the patients (77.6%) followed by DQB1*0302 allele (10.2%). The highest HLA-DQB risk for CD development was found in patients carriers a DQ2.5/DQ8 genotype (1/10), followed by the patients carriers DQ2.5/DQ2.5 (1/12). Conclusion The significant differences in the frequency of HLA-DQ2 and HLA-DQ8 in Syrian patients in compared with controls and relative risks predicted demonstrated the importance role of these alleles in the development of CD in Syrian children patients.